Formulation and the in-vitro and biopharmaceutical evaluation of sustained release tablet of verapamil HCL using precirol ATO 5 through melt granulation technique - Bhagwat, Durgacharan A; Kawtikwar, Pravin S; Sakarkar, Dinesh M (Asian Journal of Pharmaceutics (AJP), 2014)
Sustained release tablet of Verapamil hydrochloride (VPH) was prepared by using Precirol ATO 5 (PREC) by direct compression of matrices prepared by using the melt granulation technique. The effect of different concentrations of PREC on the in-vitro drug release of VPH was studied by comparing it with the marketed formulation and percent release given in USP for VPH extended release tablets. Effect of release enhancers such as microcrystalline cellulose (MCC) and lactose on in-vitro drug release was also studied. Biopharmaceutical evaluation of the satisfactory formulation was also performed in order to estimate the maximum concentration of drug in plasma (Cmax), time required to reach maximum concentration (tmax), elimination rate constant (k), elimination rate constant (t1/2), area under curve (AUC(0-t) and AUC(02a), apparent volume of distribution (Vd) and mean residence time. The results showed that PREC can be utilized as the matrix forming agent to sustain the release of VPH. The results of biopharmaceutical evaluation showed that the rate of absorption appeared to be more sustained, resulting in a more uniform plasma concentration profile of VPH. More bioavailability was noted with the sustained release formulation even though the drug has substantial first pass metabolism. The results indicated that it is possible to make once-a-day sustained-release tablet of VPH by using the melt granulation technique. Key words: Biopharmaceutical evaluation, melt granulation, precirol ATO 5, sustained release, verapamil hydrochloride